2020
DOI: 10.1371/journal.pone.0238347
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer cell phenotype is altered in HIV-exposed seronegative women

Abstract: Highly exposed seronegative (HESN) individuals present a unique setting to study mechanisms of protection against HIV acquisition. As natural killer (NK) cell activation and function have been implicated as a correlate of protection in HESN individuals, we sought to better understand the features of NK cells that may confer protection. We used mass cytometry to phenotypically profile NK cells from a cohort of Beninese sex workers and healthy controls. We found that NK cells from HESN women had increased expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 70 publications
1
19
0
Order By: Relevance
“…HESN NK cells present increased expression of NKG2A, NKp30, LILRB1, and CD16, and decreased expression of DNAM-1, CD94, Siglec-7, and NKp44. These NK cells have increased ADCC, which correlates with increased CD16 [99].…”
Section: Nk Cell Responses and Development Of Memory-like Nk Cells Afmentioning
confidence: 97%
“…HESN NK cells present increased expression of NKG2A, NKp30, LILRB1, and CD16, and decreased expression of DNAM-1, CD94, Siglec-7, and NKp44. These NK cells have increased ADCC, which correlates with increased CD16 [99].…”
Section: Nk Cell Responses and Development Of Memory-like Nk Cells Afmentioning
confidence: 97%
“…Such high-risk subjects are referred to as HIV-exposed seronegative (HESN) individuals and include sex workers, HIV-status discordant couples, intravenous drug users, and children born to untreated HIV-infected mothers. Relative resistance to HIV infection is likely multi-factorial and several studies have identified innate immune and anti-inflammatory factors, HIV-specific T- and B-cell responses, increased regulatory T- and B-cell activity as well as genetic and epigenetic correlates to this phenotype [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…TIGIT expression by memory T-cells correlated with HIV disease progression, with T-cells from elite controllers expressing lower levels of TIGIT than viremic individuals or even ART-treated individuals [ 171 ], and a blockage of TIGIT expression by NK cells increased their anti-tumoral cytotoxicity by preventing cell exhaustion [ 170 ]. In Beninese HESN women, a slightly higher expression of TIGIT was found when compared to healthy donors [ 172 ]. As to whether this slight increase of TIGIT correlates with a gain of function remains to be established.…”
Section: Natural Killer Cellsmentioning
confidence: 99%
“…Studies conducted with the Beninese CSWs cohort showed that while NK cells of HESN women did not cluster into a different subset when compared to uninfected women, they expressed higher levels of CD16 (FCɣRIII) [ 172 ]. CD16 is an Fc receptor that allows binding to IgG Fc portion, and whose binding is essential to ADCC activity by NK cells [ 165 ].…”
Section: Natural Killer Cellsmentioning
confidence: 99%